Novel methodology for the detection of exercise-induced myocardial wall motion abnormalities by surface electrocardiogram during exercise test. - Michaelides, A; Massias, S; Antoniades, C; Tsiachris, D; Dilaveris, P; Aggelis, A; Liakos, C; Marinou, K; Raftopoulos, L; Soulis, D; Stefanadis, C (2011)
BACKGROUND: We investigated whether ischemia-induced wall motion abnormalities during exercise test modify electrical vector variation. METHODS: We performed treadmill exercise test and thallium 201 scintigraphy in 150 normotensives. Beat-to-beat change of direction of S wave in V(1) (reference lead) was compared with that of R wave in V(5) and aVF, representative of anterior and inferior walls, respectively. The percentage of neighboring QRS couples where S wave in V(1) and R wave in V(5) or aVF change toward the same direction (increase or decrease) constitutes V1-V5 and V1-aVF indexes. RESULTS: V1-V5 and V1-aVF indexes were significantly decreased in subjects with reversible anterior or inferior ischemia, respectively. A decrease in V1-V5 index ≥0.14 defines those with anterior wall ischemia (sensitivity, 100%; specificity, 75.5%), whereas a decrease in V1-aVF index ≥0.05 defines those with inferior wall ischemia (sensitivity, 92.3%; specificity, 61.5%). CONCLUSIONS: These novel electrocardiographic exercise test indexes improved significantly their sensitivities.